Shades of sovereignty money and the making of the state - Wilson, P. A. (Paul Anthony) (Rowman & Littlefield, 2021)
"This book traces the role of money in the creation of the state. From US independence to the establishment of the EU and the breakup of the USSR and beyond, Wilson examines changing attitudes about monetary sovereignty, arguing for a more rational attitude toward money as a means of transactions rather than as a symbol of national identity"--